2008
DOI: 10.1681/asn.2008010014
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alkaline Phosphatase Predicts Mortality among Maintenance Hemodialysis Patients

Abstract: Several observational studies have demonstrated that serum levels of minerals and parathyroid hormone (PTH) have U-or J-shaped associations with mortality in maintenance hemodialysis patients, but the relationship between serum alkaline phosphatase (AlkPhos) and risk for all-cause or cardiovascular death is unknown. In this study, a 3-yr cohort of 73,960 hemodialysis patients in DaVita outpatient dialysis were studied, and the hazard ratios for all-cause and cardiovascular death were higher across 20-U/L incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
228
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(256 citation statements)
references
References 49 publications
22
228
2
4
Order By: Relevance
“…Our study revealed that total serum ALP levels were associated with higher all-cause and cardiovascular mortality in PD patients, independent of serum calcium, phosphorus, iPTH, and liver enzymes (AST and ALT). It was reported that bone mineral disease characteristics are different in PD and HD (9) and that bone microarchitecture is more severely affected in patients on HD than patients receiving PD (8); however, our study indicated that the association between ALP and mortality in PD patients is similar with the previous study in HD patients (6).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our study revealed that total serum ALP levels were associated with higher all-cause and cardiovascular mortality in PD patients, independent of serum calcium, phosphorus, iPTH, and liver enzymes (AST and ALT). It was reported that bone mineral disease characteristics are different in PD and HD (9) and that bone microarchitecture is more severely affected in patients on HD than patients receiving PD (8); however, our study indicated that the association between ALP and mortality in PD patients is similar with the previous study in HD patients (6).…”
Section: Discussionsupporting
confidence: 53%
“…Another analysis of the Dialysis Outcomes and Practice Patterns Study database showed that elevated serum ALP levels were associated with higher risk of hospitalization and death in HD patients, independent of serum calcium, phosphorus, and PTH levels, without including adjustment for liver function (5). Subsequently, using the DaVita and Hemodialysis Study databases, researchers found that high serum ALP levels in HD patients, adjusted for serum calcium, phosphorus, PTH, and liver enzymes, were indeed associated with higher mortality (6,7). However, little is known about PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with ESRD and in the general population, higher serum levels of AlkPhos and phosphate are associated with increased all-cause and cardiovascular mortality (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent studies support the hypothesis that these associations are mediated by vascular calcification (14,15), although medial calcification is seen almost exclusively in patients with advanced kidney disease and diabetes and not in the general population (16).…”
mentioning
confidence: 99%
“…Lomashvili et al (5) reported that vascular damage can induce expression of tissuenonspecific alkaline phosphatase (AlkPhos), which per se hydrolyzes and inactivates inorganic pyrophosphates, a process that can enhance vascular calcification. We recently showed that higher serum AlkPhos levels in maintenance hemodialysis (MHD) patients were independently associated with increased all-cause and cardiovascular mortality in approximately 74,000 MHD patients, even after adjustment for surrogates of nutrition, inflammation, minerals, serum parathyroid hormone (PTH), and liver enzymes (10). Nevertheless, the pathophysiologic link between increased AlkPhos level and mortality in MHD patients is not clear.…”
mentioning
confidence: 99%